The TwistDock workflow for evaluation of bivalent Smac mimetics targeting XIAP - Huang Q; Peng Y; Peng Y; Wei D; Wei Y; Feng S (Dove Medical Press, 2019)
Qingsheng Huang,1 Yin Peng,2 Yuefeng Peng,1,3 Dan Wei,4 Yanjie Wei,1 Shengzhong Feng11Joint Engineering Research Center for Health Big Data Intelligent Analysis Technology and Center for High Performance Computing, Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences, Shenzhen, Guangdong, People’s Republic of China; 2Department of Pathology, Shenzhen University School of Medicine, Shenzhen, Guangdong, People’s Republic of China; 3Center for Drug Evaluation and Research (CDER), Food and Drug Administration (FDA), Silver Spring, MD 20903, USA; 4School of Computer Science and Technology, Hangzhou Dianzi University, Hangzhou, People’s Republic of ChinaPurpose: Mimetics based on Smac, the native inhibitor of XIAP, are promising drug-candidates for the treatment of cancer. Bivalent Smac mimetics inhibit XIAP with even higher potency than monovalent mimetics, but how to optimize the linker that tethers the two monovalent binding motifs remains controversial.Methods: To construct an ensemble of bivalent complex structures for evaluating various linkers, we propose herein a workflow, named TwistDock, consisting of steps of monovalent docking and linker twisting, in which the degrees of freedom are sampled focusing on the rotation of single bonds of the linker.Results: The obtained conformations of bivalent complex distribute randomly in the conformational space with respect to two reaction coordinates introduced by the linker, which are the distance of the two binding motifs and the dihedral angle of the two planes through the linker and each of the binding motifs. Molecular dynamics starting from 10 conformations with the lowest enthalpy of every complex shows that the conformational tendency of the complex participated by compound 9, one of the compounds with the largest binding affinity, is distinct from others. By umbrella sampling of the complex, we find its global minimum of the free energy landscape. The structure shows that the linker favors a compact conformation, and the two BIR domains of XIAP encompass the ligand on the opposite sides.Conclusion: TwistDock can be used in fine-tuning of bivalent ligands targeting XIAP and similar receptors dimerized or oligomerized.Keywords: molecular modeling, docking, molecular dynamics simulation, MMPBSA, umbrella sampling